EFFECT OF SEED PRIMING WITH BOTANICAL LEAF EXTRACTS ON SEED QUALITY AND YIELD OF MAIZE HYBRID, COH(M) 4 - S. SRIMATHI, J. GOKULAKRISHNAN; M. PRAKASH* (The Journal of Research ANGRAU, 2021)
The investigation was carried out to study the effect of seed priming with botanical leaf extracts on seed quality and yield of maize hybrid, COH(M) 4. The seeds of maize hybrid, COH(M) 4 were primed with various leaf extracts at 10% concentration viz., Papaya (Carica papaya), Pungam (Pongamia pinnata), Prosopis (Prosopis juliflora), Adathoda (Justicia adhatoda), Tulsi (Ocimum tenuiflorum), Neem (Azadirachta indica) and Moringa (Moringa oleifera) along with a control. The study revealed that the seeds primed with 10% prosopis leaf extract followed by 10% moringa leaf extract recorded higher seed quality characters like germination percentage, speed of germination, seedling length, dry matter production, vigour index I and II. In the field evaluation, seeds primed with 10% prosopis leaf extract followed by 10% moringa leaf extract recorded higher seed yield and yield attributing parameters like cob length and girth, total number of seeds cob-1, 100 grain weight, grain yield per ha and harvest index.